Early Laparoscopic Versus Open Cholecystectomy for Acute Cholecystitis - AL-Nasir, Mumtaz K. H. (AL-Kindy College Medical Journal, 2007)
Background: Acute cholecystitis is common surgicalproblem, which was treated previously by conservativetreatment .Later early open has been introduced as analternative to interval for treatment of acute cholecystitis.Early open was found to be a safe, successful withcomparable postoperative complication rate. With theadvent of laparoscopy laparoscopic have been used forchronic cholecystitis and became the first line oftreatment. New reports have shown that laparoscopic canbe used as an alternative to open for surgical treatment ofacute cholecystitis.Objectives: to compare the success, safety of earlylaparoscopic versus early open as a primary treatment ofacute cholecystitis.Methods: out of 68 patients were treated for clinicalacute cholecystitis between January 2002 and February2004 in the department of surgery, at Al – Kindy teachinghospital. A total of 62 patients underwent early for acutecholecystitis as soon as possible after diagnosis. Thepreferred preoperative imaging technique was ultrasound.30 (48.3%) of the operations were attemptedlaparoscopically, whereas the remaining 32 patients(51.7%) underwent initial open .Results: The mean operative time for the open caseswas 75 minutes versus 60 minutes for the laparoscopicgroup. There was no perioperative mortality in eithergroup. The incidence of conversion to open was 10% (3patients). Surgical complications related to laparoscopicand open occurred in 2 (6.6%) and 3 (9.3%) cases,respectively. There was no difference between the openand laparoscopic groups in regard to the majorpostoperative complications.Conclusion: The current study shows that early(whether performed by open or laparoscopically) is asafe and effective treatment for acute cholecystitis. Lowconversion rates can be maintained with strict guidelinesfor appropriate patient selection, adequate experience,and proper laparoscopic technique.